2020
DOI: 10.1055/a-1079-4915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Follow-Up Results of Adrenal Incidentaloma

Abstract: It is recommended that adrenal incidentaloma patients should be monitored for radiological changes, increase in size and new functionality that may occur in the future, even if they are benign and nonfunctional at the initial evaluation. Our aim is to evaluate the key clinical characteristics of adrenal incidentaloma patients focusing on changes during follow-up and associated clinical outcomes. A total of 755 patients (median age: 56 years), with an adrenal incidentaloma > 1 cm and underwent functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
2
21
1
3
Order By: Relevance
“…Only 0.9% of adenomas grew by at least 10 mm when the mean follow-up was shorter than 24 months, compared with 2.9% of adrenal tumors followed for at least 24 months ( 2 ). However, in a recent study, 11.7% of the patients had an increase ≥10 mm at 24 month follow-up ( 21 ) that was similar to our cohort, where tumor enlargement (≥10 mm) occurred in 8.9% of patients. Some previous observations proposed that adenomas with a baseline size of at least 25 mm were less likely to grow than smaller adenomas (< 25 mm) suggesting that patients with larger tumors were involved later in their course of natural history ( 2 ); however, we did not observe such differences.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Only 0.9% of adenomas grew by at least 10 mm when the mean follow-up was shorter than 24 months, compared with 2.9% of adrenal tumors followed for at least 24 months ( 2 ). However, in a recent study, 11.7% of the patients had an increase ≥10 mm at 24 month follow-up ( 21 ) that was similar to our cohort, where tumor enlargement (≥10 mm) occurred in 8.9% of patients. Some previous observations proposed that adenomas with a baseline size of at least 25 mm were less likely to grow than smaller adenomas (< 25 mm) suggesting that patients with larger tumors were involved later in their course of natural history ( 2 ); however, we did not observe such differences.…”
Section: Discussionsupporting
confidence: 89%
“…We collected data about additional CT findings at the follow-up CT scan. At follow-up, 37.9% of patients had additional CT changes in kidneys, 21 We observed atherosclerotic changes and dilatation of aorta (N=1 in BMI < 25 kg/m 2 , N=3 in BMI 25-30 kg/m 2 and N=2 in BMI < 30 kg/m 2 ). In BMI group 25-30 kg/m 2 we observed one patient with lung nodules, one with Bochdalek's hernia and one with fracture of eleventh thoracic vertebra.…”
Section: Other Findings On Ct At Follow-upmentioning
confidence: 70%
“…Functioning tumours traditionally will be managed by surgical approach. On the other hand, non-functional adrenal incidentalomas with no radiological features of malignancy and of small size will normally be monitored by radiological examination and functionally to see if there are any clinical progression [191]. An increase in size and development of functionality during follow-up in patients with adrenal incidentalomas will normally lead to biopsy and surgical resection.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…However, this is probably a consequence of several factors: (1) a type 2 error, due to low rates of ACS and cardiometabolic comorbidities development; and (2) short follow-up period, as the development of comorbidities is likely directly associated not only with the serum cortisol post-DST level but also with the time of exposure. Several previous studies, however, have observed an increased cardiometabolic risk in patients with AIs and ACS [ 22 , 23 ]. Our data support this association as, despite the lack of statistically significant differences, a higher proportion of new comorbidities in patients who progressed to ACS than in patients who remained suppressible after DST was also observed ( Table A1 ).…”
Section: Discussionmentioning
confidence: 93%